Cititorul e în altă parte (CITITORI ȘI LECTURI. CERCETĂRI COMPARATISTE, 2026)
Madena Popa explores the theme of the reader in Milan Kundera’s Life is Elsewhere. The study analyzes how Jaromil, the protagonist, fails to distinguish between fiction and reality, falling into the trap of "lyrical identification." By comparing Jaromil with other characters like his mother or the painter, the author highlights the dangers of using literature as a mere narcissistic mirror. Ultimately, the study suggests that a "Model Reader" must transcend lyricism for objective, aesthetic lucidity. THIS ABSTRACT IS GENERATED WITH ARTIFICIAL INTELLIGENCE.